2020
DOI: 10.3897/zookeys.963.52234
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of benthic marine mollusks of the Strait of Magellan, Chile (Polyplacophora, Gastropoda, Bivalvia): a historical review of natural history

Abstract: An increase in richness of benthic marine mollusks towards high latitudes has been described on the Pacific coast of Chile in recent decades. This considerable increase in diversity occurs specifically at the beginning of the Magellanic Biogeographic Province. Within this province lies the Strait of Magellan, considered the most important channel because it connects the South Pacific and Atlantic Oceans. These characteristics make it an interesting area for marine research; thus, the Strait of Magellan has his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 82 publications
0
6
0
2
Order By: Relevance
“…3), se puede observar que la riqueza de isla Gonzalo (51 taxa) es alta, considerando que sólo se han podido muestrear dos puntos de toda la isla. Por ejemplo, a lo largo de todo el Estrecho de Magallanes se han reportado 303 especies (Aldea et al 2020). Por lo tanto, el archipiélago Diego Ramírez presentaría el 16,8% de las especies citadas para el Estrecho de Magallanes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…3), se puede observar que la riqueza de isla Gonzalo (51 taxa) es alta, considerando que sólo se han podido muestrear dos puntos de toda la isla. Por ejemplo, a lo largo de todo el Estrecho de Magallanes se han reportado 303 especies (Aldea et al 2020). Por lo tanto, el archipiélago Diego Ramírez presentaría el 16,8% de las especies citadas para el Estrecho de Magallanes.…”
Section: Discussionunclassified
“…En este sentido, es importante seguir abordando estudios de biodiversidad en más localidades dentro de la provincia Magallánica, particularmente sitios poco visitados y que representan un gran vacío de información, como por ejemplo la zona expuesta Pacífica de los canales, el archipiélago cabo de Hornos y el archipiélago Diego Ramírez. Esta información permitiría (Valdovinos, 1999), Provincia Magallanica (Linse, 1999;Sirenko, 2006), Estrecho de Magallanes (Aldea et al 2020) e islas Diego Ramirez (este estudio).…”
Section: Discussionunclassified
“…It is essential to highlight that, despite the research efforts in Antarctica and the SO in the last decades in generating knowledge in biodiversity, there are still many poorly-sampled and -studied areas and habitats. In this regard, the intertidal and shallow subtidal environments of Antarctica and Subantarctic environments are considerably less well-sampled than either the surrounding deep sea ( Brandt et al 2014 , Ojeda et al 2014 , Griffiths and Waller 2016 , Rosenfeld et al 2017 , Aldea et al 2020 , Jossart et al 2023 ). Likewise, in continental environments, recent studies have identified important sampling gaps in Antarctica and Subantarctic ecoregions ( Chown and Convey 2016 , Maturana et al 2019 , Ganan et al 2021 , Hawes et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Subantarctic environments represent a large and remote geographic area and, due to its extreme conditions (climatic and oceanographic) ( Griffiths and Waller 2016 ), it denotes a challenge when undertaking biodiversity inventories. For example, in the Magellanic Subantarctic ecoregion, it has been described that the diversity of representative and moderately known groups, such as molluscs, would be underestimated ( Aldea et al 2020 , Rosenfeld et al 2020 ). In addition, with the progress of molecular tools to date, new lineages continue to be detected in both invertebrates and vertebrates ( Gonzalez-Wevar et al 2018 , Maturana et al 2021 , Rozzi et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The species is not reported in recent papers dealing with Leptochitonidae from Chile ( Sirenko 2006 ; Schwabe 2009 ; Schwabe and Sellanes 2010 ; Sirenko 2015 ; Sirenko and Sellanes 2016 ), but it is still (erroneously) reported in various lists. Recently, Aldea et al (2020) reported L. cullierti as a dubious species. In conclusion, at least as far as concerns living species, Lepidopleurus is presently a monotypic genus.…”
Section: Introductionmentioning
confidence: 99%